Changes in the forest structure of the Bashkortostan Republic over two decades - Baiturina Regina; Gabdelkhakov Aydar; Gabdrakhimov Kamil; Yanbaeva Vasilina (Metsanduslikud Uurimused, 2022)
This paper aimed to study the distribution of the main tree species in the Republic of Bashkortostan (RB) in a transforming climate and compare the results for the last decades. The analysis was based on the forest fund data, forest management documents, route surveys and field studies, and conducted by generally established forestry methods. The trial plots had identical soil conditions. The paper considers the impact of climate on the forest resources of the RB located at the junction of the Urals with the West Siberian Lowland, the Cis-Ural plain and steppe belt with diverse vegetation. The floristic composition of the republic is varied and includes about 1700 species of higher plants. Comprehensive research was followed by field results comparison. In 1998–2018, the area of soft-leaved species, primarily Betula pendula Roth and Tilia cordata Mill. increased by 70.8 (39%) and 74.2 thousand hectares (32%), respectively; the share of coniferous Picea and Abies declined by 57.9 thousand hectares – 15%, short-trunk Quercus robur L. lowered by 34% and the high-trunk one decreased by 6% and Acer by 8%. The conducted study suggests a significant increase in destructive insects. Spruce forests will suffer, because there is a reduction in the area by 20% over 20 years. Thus, there has been a gradual displacement of forest species. Forestry challenges and the sustainable ecological balance both in the republic and the planet as a whole require further joint efforts of scientific and environmental organisations and authorities for forecasting transformational processes and developing measures to address them.